α-amination of aldehydes catalyzed by in situ generated hypoiodite - Tian, Jie-Sheng. (2013)
The metal-free amination of different aldehydes is catalyzed by hypoiodite, which is generated by employing commercially available sodium percarbonate as the co-oxidant. This approach has several advantages: it is a metal-free oxidation that works under mild reaction conditions; furthermore, it has a wide substrate scope and does not give toxic by-products from the co-oxidant that is used.